Endoscopic Surgery for Third Ventricular Colloid Cysts in the Absence of Hydrocephalus- a feasibility study - Sharifi, Guive; Hosseinzadeh Bakhtevari, Mehrdad; Samadian, Mohammad; Jabbari, Reza; Rezaei, Omidvar (International Clinical Neuroscience Journal, 2014)
Purpose: The aim of this study was to investigate the feasibility and effectiveness of endoscopic neurosurgery for patients with third ventricular colloid cysts without ventriculomegaly. Methods: Seventy-one patients with third ventricular colloid cysts were identified and recruited to this study. Eighteen of these patients did not have concomitant hydrocephalus and underwent primary endoscopic surgery for cyst resection. The surgical technique, the success rate, and patients’ outcome were assessed and compared with 53 hydrocephalic patients who underwent similar procedures. Results: The ventricular compartments were successfully cannulated and gross total resectin of the colloid cysts was achieved in all patients. There were no operative complications related to the endoscopic procedure. Two patients required subsequent intervention for hydrocephalus. The success rate for endoscopic surgery in non-hydrocephalic patients was similar to its value in patients with hydrocephalus. Conclusion: Endoscopic resection of third ventricular colloid cyst in patients without hydrocephalus seems to be feasible, effective and not contraindicated.